2017
DOI: 10.1111/bcpt.12793
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, Dysbiosis and Expression of Inflammatory Cytokines are Sequential Events in the Development of 5‐Fluorouracil‐Induced Intestinal Mucositis in Mice

Abstract: The chemotherapeutic agent 5-fluorouracil (5-FU) causes intestinal mucositis with severe diarrhoea, but the pathogenesis is not fully understood. In this study, we investigated the pathogenic effects of 5-FU in mice, focusing on apoptosis, enterobacteria and inflammatory cytokines. Repeated administration of 5-FU caused severe intestinal mucositis on day 6, accompanied by diarrhoea and body-weight loss. TNF-α expression increased 1 day after exposure to the drug, and spiked a second time on day 4, at which poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…Repeated administration of 5‐FU significantly decreased the abundances of Firmicutes and Actinobacteria , which are mostly comprised of gram‐positive bacteria, while significantly increasing the abundances of Bacteroidetes and Proteobacteria , which are mostly gram‐negative bacteria. Similar alterations to the intestinal microbiota were recently reported in human subjects during cancer chemotherapy and in experimental animals receiving 5‐FU treatment . Toll‐like receptor 4 signalling is reportedly involved in the pathogenesis of anti‐cancer agent‐induced gastrointestinal toxicities .…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Repeated administration of 5‐FU significantly decreased the abundances of Firmicutes and Actinobacteria , which are mostly comprised of gram‐positive bacteria, while significantly increasing the abundances of Bacteroidetes and Proteobacteria , which are mostly gram‐negative bacteria. Similar alterations to the intestinal microbiota were recently reported in human subjects during cancer chemotherapy and in experimental animals receiving 5‐FU treatment . Toll‐like receptor 4 signalling is reportedly involved in the pathogenesis of anti‐cancer agent‐induced gastrointestinal toxicities .…”
Section: Discussionsupporting
confidence: 78%
“…We previously showed that apoptosis can be detected in the intestinal crypt within 24 hours of the first injection of 5‐FU, suggesting that apoptosis is a critical event for the initiation of 5‐FU‐induced intestinal mucositis . In addition, secondary inflammatory responses are believed to occur resulting in the disruption of the epithelial barrier, which is induced by apoptosis and hypoproliferation . Indeed, several studies have demonstrated that inflammatory responses such as increases in MPO activity and inflammatory cytokine expression are involved in the pathogenesis of 5‐FU‐induced intestinal mucositis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations